Surgical site infection in benign abdominal gynaecological surgeries - Kodiyath, Haritha Kizhakke; Ramakrishnan, Kunnath; Jacob, Kadaviparambil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Surgical site infection is the commonest complication after gynecological surgeries. Limited studies have been done in India to know the magnitude of the problem. This study aims to know the incidence of surgical site infection, analyze the risk factors and identify the causative organisms. Methods: A prospective observational study .All women who underwent abdominal surgeries for benign pathologies in department of obstetrics and gynecology, Government medical college, Thrissur from April 2016 to March 2017, were included in the study women more than 80 years old, evidence of infection preoperative or within 48 hours of surgery, laparoscopy procedures unless combined with open surgeries and emergency surgeries were excluded. Results: The incidence of SSI was found to be 7.9%. Re suturing had to be done in 24 patients. The risk factors found to be significant were age more than 50 years ,patients with education <7th std, diabetes, BMI>30,pre hospital stay >10 days, ASA score >3, duration of surgery >2 hours and peri-operative blood transfusion. Staphylococcus aureus was the most common causative organism and was sensitive to amikacin, vancomycin, cloxacillin and its combinations. Conclusions: SSI pose a significant problem in the post operative period that can affect recovery. It was associated with multiple predisposing factors which could be prevented if these risk factors are identified early and appropriate measures are adopted to support host defense system in the peri operative time.